Interaksieprosesontleding in verpleging - D. Du Toit (AOSIS, 1984)
Nursing is a humanistic science which concerns itself with man in need. Nursing has also long been recognised as a science with its own defined scientific knowledge unique to nursing. In order that nursing could grow as a science it was necessary to delve into other humanistic sciences for knowledge relevant to nursing. This knowledge should be incorporated into nursing in order to contribute to development of scientific nursing theory. This knowledge should also be applied to the advantage of nursing. In this article the use of certain methods and techniques normally used in group dynamics, a branch of Sociology, and how these methods and techniques can be usefully applied to nursing, are speculated on. Attention is given to the possibility of the application of Bales's technique of interaction process analysis to various fields of nursing.